Planning for development : the Caroni Region preliminary draft development plan. Development planning series ; no. T5. - Government of the Republic of Trinidad and Tobago. Ministry of Finance, Planning and Development. (Town and Country Planning Division., 2011)
Describes the functions of the region, development plans, physical characteristics, natural resources, land use, socio-economic environment, and presents a regional analysis with problems, development potential and proposals.